Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.1 - The Algebra of Functions - Exercise Set: 28

Answer

$H(x) = f(h(x))$

Work Step by Step

$f(x) = 3x$ $h(x) = x^2 + 2$ $H(x) = 3x^2 + 6$ $H(x) = 3(x^2 + 2)$ therefore $H(x) = f(h(x))$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.